Does the involvement of first-year residents have a negative impact on the performance of a newborn hearing screening program?. (November 2020) - Gallus, Roberto; Rizzo, Davide; De Luca, Laura Maria; Melis, Andrea; Kihlgren, Caterina; Parente, Paolo; Anzivino, Roberta; Frezza, Simonetta; Priolo, Francesca; Bussu, Francesco; Conti, Guido
Abstract: Objectives: We aimed to evaluate the efficiency of our hearing screening program, prior to hospital discharge, together with the consistency of our teamwork including first year residents by assessing a learning curve for the operators involved. Methods: We evaluated all the data collected during the first stage of the screening program of all non-NICU neonates from March 2009 to July 2013, analyzing by means of a linear regression model, the monthly referral rate for the whole period of activity of each group of residents. Results: performances of each group of screeners were statistically different (chi square test p < 0.005). The nptrend test showed that group 2 (p = 0.01) and group 4 (p = 0.01) reached a statistical significance in higher and lower referral rates respectively. No statistical differences were found in other groups (Group 1 p = 0.161; Group 3 p = 0.853). Conclusion: Despite a statistically significant difference in the performances between the groups of residents, the referral rates for each group (range 6.18%–9.29%) and the overall referral rate for the whole period (7.84%) agree with the values commonly reported for TEOAEs in the literature. It means that our screening program is reasonably effective despite a yearly turnover of operators.